2014
DOI: 10.1016/j.grj.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Chloride partitioning and solubility in hydrous phonolites from Erebus volcano: A contribution towards a multi-component degassing model

Abstract: International audienceWe present results from a series of experiments on the partitioning of chlorine between a hydrous fluid phase and a phonolitic melt that we then use to model specific aspects of volcanic degassing. Experiments were performed from 250 to 10 MPa on a phonolite from Erebus lava lake, Antarctica, at 1000 °C near the QFM solid buffer. Only one of 48 experimental samples shows coexistence of low-density vapour and high-density brine in the fluid phase while 35 samples are unambiguously in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
(198 reference statements)
0
3
0
Order By: Relevance
“…The propagated errors are plotted in figures 4-8. Previous studies have shown that these propagated errors often overestimate the absolute error and thus can be considered maximum values (e.g., Alletti et al, 2014;Cadoux et al, 2018). Finally, Quizapu and Kelud both contain trace amounts of apatite (<1 vol%) and Quizapu contains ~2 vol% hornblende Drake 1992 Ruprecht et al, 2012;Jeffery et al, 2014;Cassidy et al, 2016;2019;First et al 2021).…”
Section: Fluid Concentration Of Halogen (Ppm)= Mass (G) Of Halogen In Fluid/ Corrected Final Fluid Mass (G) X 10mentioning
confidence: 98%
“…The propagated errors are plotted in figures 4-8. Previous studies have shown that these propagated errors often overestimate the absolute error and thus can be considered maximum values (e.g., Alletti et al, 2014;Cadoux et al, 2018). Finally, Quizapu and Kelud both contain trace amounts of apatite (<1 vol%) and Quizapu contains ~2 vol% hornblende Drake 1992 Ruprecht et al, 2012;Jeffery et al, 2014;Cassidy et al, 2016;2019;First et al 2021).…”
Section: Fluid Concentration Of Halogen (Ppm)= Mass (G) Of Halogen In Fluid/ Corrected Final Fluid Mass (G) X 10mentioning
confidence: 98%
“…The D-Compress thermodynamic model is based on experimentally determined solubility laws for key species (H 2 O, CO 2 , H 2 , SO 2 , H 2 S) and redox equilibrium equations for gaseous carbon-, oxygen-, hydrogen-, and sulphur-bearing species (Burgisser and Scaillet 2007;Burgisser et al 2012;Alletti et al 2014). Given relative proportions of these volatiles as gas ratios, CO 2 /H 2 O, CO 2 /CO, OCS/SO 2 , CO 2 /SO 2 , and optionally CO 2 /HCl, and assuming that the gases are at equilibrium, D-Compress calculates equilibrium temperature at a given pressure.…”
Section: D-compressmentioning
confidence: 99%
“…However, interpreting degassing history is complicated since the composition of the gas phase changes as magma ascends. With an increasing body of experimental work to understand the solubility and redox relationships of different volatile species, thermodynamic models for degassing that incorporate empirical solubility laws are becoming available (Burgisser et al 2012(Burgisser et al , 2015Alletti et al 2014).…”
Section: Introductionmentioning
confidence: 99%